Inflation uncertainty, disagreement and monetary policy: evidence from the ECB survey of professional forecasters - Glas, Alexander; Hartmann, Matthias (Discussion paper series, 2016)
We analyze the determinants of average individual in ation uncertainty and disagreement based on data from the European Central Bank's Survey of Professional Forecasters. We empirically confirm the implication from a theoretical decomposition of in ation uncertainty that disagreement is an incomplete approximation to overall uncertainty. Both measures are associated with macroeconomic conditions and indicators of monetary policy, but the relations differ qualitatively. In particular, average individual in ation uncertainty is higher during periods of expansionary monetary policy, whereas disagreement rises during contractionary periods.
Keywords: Arbeitspapier; Graue Literatur